Family Characteristics as Determinants of Mental Health in Adolescents - Maglica, Toni; Ercegovac, Ina Reić; Ljubetić, Maja (European Journal of Mental Health, 2021)
The family environment is considered to be a micro-ecological system with numerous risk and protective factors for mental health. The goal of this research was to determine how different functional and/or structural family characteristics affect some indicators of mental health in adolescents. A number of 1,239 adolescents (ages 15–19) participated in the research. General Data Questionnaire, Family Life Satisfaction Scale, Family Communication Scale, Positive Mental Health Scale, Anxiety, Depression and Stress Scale, and Stressful Events in the Family Checklist, were applied. The results indicated no connection between sociodemographic characteristics and self-assessed satisfaction. Adolescents with older parents were less satisfied with their family and familial communication. Gender differences in mental health were confirmed, mostly to the detriment of girls. The mother’s age and the father’s level of education significantly correlate with individual mental health. Adolescents with older mothers reported lower mental health. Adolescents with fathers of lower educational status reported higher stress and depression level. Stress within the family proved to be significant in explaining adolescents’ mental health, especially due to financial issues, and conflicts among family members. Finally, the results indicated that family communication and satisfaction, with the control of sociodemographic characteristics and stress in a family, additionally explain the significant part of the variance in adolescents’ mental health.